ANALYSIS OF TRANSPARENCY IN ZAKAT MANAGEMENT ORGANIZATIONS TO MAXIMIZE ZAKAT POTENTIAL AT BAZNAS PAPUA PROVINCE - Pangkali, Avilla Joan (International Journal of Social Service and Research, 2025)
This study examines the transparency of zakat management in maximizing Zakat in the Papua provincial baznas. Ministry of Home Affairs said the majority of Muslims are from non-indigenous Papuan tribes (439,337 people or 15.51%), while the rest are from indigenous Papuan tribes (10,759 people, or 0.38%). BAZNAS Papua Province, as a philanthropic institution that functions to manage zakat funds, and one of the goals of zakat funds is to realize community welfare and poverty alleviation. Qualitative research was carried out in order to analyze the transparency of the zakat management organization in the Papua provincial baznas, using SWOT analysis (Strenghts Weaknesses Opportunities Treaths). To answer this question, this research was conducted by observation in the field and direct interviews at the Papua Provincial Baznas. In addition, the researcher also used primary data and secondary data from various books and searches from online data. The results of this study show that the collection, distribution and utilization of zakat, infak and alms at the Baznas of Papua province at the Planning Organizing Actuating Controlling (POAC) stage has been running quite well. Furthermore, the results of the SWOT analysis using the matrix and SWOT diagram show that the Baznas of Papua province has done its job well, including, increasing public trust, optimizing zakat collection, increasing distribution evidence, better quality of zakat, as well as improving the image and reputation where the position is very favorable for the Papua Provincial Baznas with the existence of internal strength and external opportunities.